FAP Associated Papillary Thyroid Carcinoma: A Peculiar Subtype of Familial Nonmedullary Thyroid Cancer. (1st December 2015) - Cetta, Francesco
Abstract : Familial Nonmedullary Thyroid Carcinoma (FNMTC) makes up to 5–10% of all thyroid cancers, also including those FNMTC occurring as a minor component of familial cancer syndromes, such as Familial Adenomatous Polyposis (FAP). We give evidence that this extracolonic manifestation of FAP is determined by the same germline mutation of the APC gene responsible for colonic polyps and cancer but also shows some unusual features (F : M ratio = 80 : 1, absence of LOH for APC in the thyroid tumoral tissue, and indolent biological behaviour, despite frequent multicentricity and lymph nodal involvement), suggesting that the APC gene confers only a generic susceptibility to thyroid cancer, but perhaps other factors, namely, modifier genes, sex-related factors, or environmental factors, are also required for its phenotypic expression. This great variability is against the possibility of classifying all FNMTC as a single entity, not only with a unique or prevalent causative genetic factor, but also with a unique or common biological behavior and a commonly dismal prognosis. A new paradigm is also suggested that could be useful (1) for a proper classification of FAP associated PTC within the larger group of FNMTC and (2) for making inferences to sporadic carcinogenesis, based on the lesson from FAP.